General practitioners' willingness to participate in research networks in Germany. (3rd April 2022) - Virnau, Larissa; Braesigk, Annett; Deutsch, Tobias; Bauer, Alexander; Kroeber, Eric Sven; Bleckwenn, Markus; Frese, Thomas; Lingner, Heidrun
Abstract: Objectives: To investigate general practitioners' (GPs') willingness to participate in long-term medical research and in research networks (RNs). Design and setting: Cross-sectional survey among German GPs around Halle-Wittenberg and Leipzig in 2020. Subjects: Random sample of 905 GPs. Main outcome measures and results: Response rate 37%, 69% female. Overall, 57% were interested in participating in medical research, 34% in an active role in a RN. Interest in RN participation was positively associated with male sex, younger age, previous experiences in medical research, being involved in teaching undergraduates, and having qualification in a further specialty. Main motivators were improving patient care, giving a more realistic picture of GP care, and carrying out research on topics within their own interest areas and a reliable contact person at the leading institution. Most GPs were not afraid of reduced earnings; however, time investment was the main barrier for participation. GPs were willing to dedicate twice as much time to research when remuneration was offered. High rated topics were polypharmacy, chronic diseases, drug safety and adverse drug reactions. Conclusion: GPs are interested to participate in practice-based research. The study results providing useful and generalizable insights in barriers and motivators should be considered when building and running GP-RNs. KEY POINTS: There is a difference between general practitioners' (GPs') overall interest in clinical research and their job and socio-demographic related readiness to participate in research networks (RNs). GPs are interested in RNs when it is a resource of and leading to enhanced patient-oriented care. GPs are willing to dedicate twice as much time to research when remunerated. GPs need a reliable counterpart within the leading institution.